Ibad Al-Rahman Memberi Terapi Terhadap Tekanan Jiwa - M. Idris Hasibuan (Jurnal Al-Muqaranah : Jurnal Perbandingan Hukum dan Mazhab, 2017)
God offers a concept that has been considered standard in anticipation of the problems faced by humans so as not to stress the concept of Ibad al-Rahman with ten kinds of criteria and the five major priorities that God gave to the servants who wish to as Ibad al-Rahman. And this concept has been able to reduce stress crisp effectual preformance faced by a person, provided that any person practicing the ten criteria. Kata Kunci : Ibad, ar-Rahman, Tekanan, Jiwa.